Pengaruh Penggunaan Biokoagulan Jamur Lapuk Putih (Trametes Versicolor) Terhadap Penurunan Kadar Phospat (Po4) Pada Limbah Cair Efluent Rumah Sakit Kusta - Utari, Sri; Wulandari, Ria (JURNAL KESEHATAN TERAPAN, 2026)
The effluent wastewater from Leper Hospitals has pollution potential, particularly due to Phosphate (PO4​) compounds, which can trigger eutrophication in receiving waters. Conventional treatment methods often produce excessive chemical sludge. Therefore, an effective and environmentally friendly treatment alternative is needed, namely through biocoagulation using the extract of the White Rot Fungus (Trametes versicolor). This study aims to determine the effectiveness and optimum dosage of the Trametes versicolor biocoagulant extract in reducing the PO4​ level in the Leper Hospital effluent wastewater.This research employed an experimental design using a Completely Randomized Design (CRD) consisting of [Number] biocoagulant dose treatments (e.g., D0​ to D4​) and [Number] replicates. Coagulation-flocculation tests were conducted using the Jar Test method with a contact time of [Specify Time]. PO4​ levels were measured using UV-Vis Spectrophotometry. Data were statistically analyzed using ANOVA followed by a Post Hoc Test [Specify Test, e.g., DMRT/Tukey] to compare the effect between treatments. The initial analysis results showed that the PO4​level in the effluent wastewater was [C0​ Value, e.g., 15.5 mg/L], exceeding the quality standard. The Jar Test results indicated that the biocoagulant dose treatments had a highly significant effect (p<0.05). The optimum dosage was found at a concentration of [Optimum Dose, e.g., 6 mL/L], which successfully reduced the PO4​ level to [Ct​ Value, e.g., 1.55 mg/L], achieving a removal efficiency of [Highest Percentage, e.g., 90.0%]. The PO4​ level at this optimum dosage met the applicable Hospital Wastewater Quality Standard. The White Rot Fungus (Trametes versicolor) biocoagulant is proven to be effective in reducing Phosphate (PO4​) levels in Leper Hospital effluent wastewater. This biological agent has the potential to be an efficient, economical, and sustainable wastewater treatment alternative.